Evaluation of the Antibacterial Activity and Effectiveness of Ciplukan Leaf Extract (Physalis angulata L.) on the Growth of Salmonella typhi Isolates - Nurhilaliyah Nurhilaliyah; Ayusti Dirga Dirga; Husnul N Khatimah; Muarifah Muarifah (VISIKES, 2026)
This study evaluated the antibacterial activity and effectiveness of ciplukan leaf extract (Physalis angulata L.) against Salmonella typhi, the causative agent of typhoid fever. The experiment was conducted using the disk diffusion method to measure inhibition zones at various extract concentrations. Phytochemical screening confirmed the presence of flavonoids, alkaloids, tannins, and saponins, which are associated with antibacterial properties. The extract showed the highest inhibitory effect at 40% concentration (25 mm) and the lowest at 5% concentration (18.67 mm). Paired t-test analysis yielded a significance value of 0.434, indicating no significant difference between the first and second observation days. These findings suggest that the antibacterial activity of ciplukan leaf extract is relatively stable and effective. Therefore, ciplukan leaf extract has potential as a natural antibacterial agent and a candidate for phytopharmaceutical development in the management of typhoid infection.